A call for revamping socio-emotional ability research in autism. (2019) - Olderbak, Sally; Geiger, Mattis; Wilhelm, Oliver
Abstract: In light of Jaswal & Akhtar's compelling argument, we argue there should instead be more focus on deficits in socio-emotional abilities. However, current research is limited by the psychometric problems with most measures. We discuss specific problems, outlining examples for theory of mind. We conclude with recommendations for new lines of research derived from findings in the individual differences literature.